Hearts of Darkness: Why Kids Are Becoming Mass Murderers and How We Can Stop It - Liebert, John and Birnes, William J. (New York Skyhorse Publishing, 2014)
From Sandy Hook, Connecticut, to Aurora, Colorado, to Tucson, Arizona, this nation has been racked from coast to coast with mass shootings perpetrated by criminals with sick minds. Authors Dr. Liebert and Dr.
Include Index
Keywords: Mass murder--Psychological aspects -- Mass murderers--Psychology -- School shootings